Wages, Amenities and Negative Attitudes - Gisela Waisman; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2012)
We exploit the regional variation in negative attitudes towards immigrants to Sweden in order to analyse the consequences of the attitudes on immigrants welfare. We find that attitudes towards immigrants are of importance: they both affect their labour market outcomes and their quality of life. We interpret the negative effect on wages as evidence of labour market discrimination. We estimate the welfare effects of negative attitudes, through their wage and local amenities, for immigrants with different levels of skills, origin, gender and age.
hdl:10398/8519
Keywords: J15; J31; J61; J71; 330; Attitudes towards immigration; Geographical Mobility; Wages; Amenities